PRAKTIK PENERAPAN AKAD WADI’AH DALAM PERBANKAN SYARIAH (STUDI KASUS BANK BTN) - Ratna Ayu Wijayanti; M.Arief Safi’i; Riki Zogik Firmansyah; Mirza Hisyam Maulana; Renny Oktafia (CV. ALIM'SPUBLISHING, 2024)
This research focuses on the implementation of the Al Wadiah concept in the State Savings Bank (BTN) in Indonesia. The concept is based on Islamic law and deals with trust and custody. The bank has integrated Al Wadiah into its savings services and manages customer funds in accordance with Sharia regulations. This study uses secondary data to analyze the implementation. The study found that BTN offers a range of savings products that emphasize the security of deposited funds. The study also identified challenges and opportunities faced by the bank in implementing the concept. These challenges include regulatory changes, educating the public and a comprehensive understanding of Sharia principles. Despite these challenges, there are opportunities for BTN to expand its range of Sharia-based services and increase public confidence in the financial system.